INTERNAL AND EXTERNAL DETERMINANTS OF PROFITABILITY: EVIDENCE FROM KBMI 4 BANKS IN INDONESIA - M. Iqbal Mashuri; Aminudin Ma'ruf (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2026)
This study analyzes factors influencing bank profitability in Indonesia, focusing on KBMI 4 category banks period 2017–2024. Profitability is measured using Return on Assets (ROA) and Return on Equity (ROE) to reflect performance from perspectives of asset utilization and shareholders. The study uses quarterly panel data and applies Fixed Effect Model with robust standard errors to examine influence of external and internal factors on bank profitability. External factors include BI Rate and inflation, while internal factors consist of operational efficiency (BOPO), credit risk measured by Non-Performing Loans (NPL), capital structure measured by Total Assets to Total Equity, and bank size. A Covid-19 dummy variable is also included to control for impact of pandemic. The results show that internal bank factors are more dominant than external macroeconomic in determining profitability. Operational efficiency and credit risk have a negative and significant effect on both ROA and ROE. Capital structure and bank size negatively and significantly affect ROA but are not significant for ROE. Meanwhile, BI Rate and inflation do not significantly influence either profitability measure. The Covid-19 variable has a positive and significant effect on ROA but not on ROE, indicating that policy support during pandemic helped maintain banks’ operational performance.